The fundamental role of behavioral skills in crystalizing the budding managers - K., Umashankar; G., Ranganatham (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2013)
The mission and vision of Management education system had been exemplary in terms of evolving a true professional and efficient leader in every student and this pristine vision had been materialized and conceptualized in the vibrant ambience of a Gurukula. In continuation, the pupils were taught not only to earn their livelihood but also the humane principles for lifetime. Indeed, the Gurukulas adopted their own experiential learning pedagogy in order to train their pupils on various domains like interpersonal skills, intrapersonal skills, and professional skills, and so on… However, their pedagogical delivery was never constrained only for creating monetary machines but to evolve a human being.To interpret in the words of Swami Vivekananda, “Man making was the mission of education but not machine making”. In this contemporaneous world of monetary appetite, the lives of the people are completely saturated and engulfed by the monetary avarice. Accordingly, the precious dimensions of life have been monopolized by the dominating dimension called the economic status.Consequently, the same tendency is percolated into the younger generation wherein their success rate is measured by the yardstick of economic success and having no consideration for the true professional fiber.Interestingly, the academic role, which is responsible for evolving holistic personality in a student, has been redefined and drifted towards the metamorphosed role of building monetary generating humanoids.In continuation, the students who witness the transit of student-hood to professional-hood invariably witness a serious crisis in the role-adoption.Moreover, their theoretical or knowledge expertise may not encompass the vast corporate dimension that include interpersonal skills, intrapersonal skills, emotional intelligence, efficacy of communication skills, leadership skills and so on… Considering the subtle deficiencies and requirements of a professional, the paper suggests a few astute practices that are derived from the philosophies of Swami Vivekananda and other management gurus.Besides, the thoughts have been linked to the contemporaneous nomenclatures like emotional intelligence, transactional analysis, self-esteem etc… Moreover, the sagacious practices that are widely observed in the corporate corridors have been suggested in order to bridge the gap.